2018
DOI: 10.1002/tox.22686
|View full text |Cite
|
Sign up to set email alerts
|

Kaempferol suppresses cell migration through the activation of the ERK signaling pathways in ARPE‐19 cells

Abstract: Kaempferol is a flavonoid with anticancer and anti-metastasis activity in different cancer-cell lines. However, the underlying mechanisms by which kaempferol acts on human retinal pigment epithelial (ARPE-19) cells remain unclear. In this study, we demonstrated that kaempferol inhibited migration and invasion in ARPE-19 cells at non-toxic dosages. We discovered that kaempferol obviously reduced the enzyme activity and protein expression of matrix metalloproteinase-2 by increasing the phosphorylated levels of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 35 publications
0
20
0
Order By: Relevance
“…Induced cell cycle arrest at the G2/M or G0/G1 phase [329,[335][336][337][338][339][340]. Reduced migration and invasion [340][341][342][343][344][345][346]. Inhibited the EMT and reduced resistance to chemotherapeutic agents [343,347].…”
Section: Kaempferolmentioning
confidence: 99%
See 1 more Smart Citation
“…Induced cell cycle arrest at the G2/M or G0/G1 phase [329,[335][336][337][338][339][340]. Reduced migration and invasion [340][341][342][343][344][345][346]. Inhibited the EMT and reduced resistance to chemotherapeutic agents [343,347].…”
Section: Kaempferolmentioning
confidence: 99%
“…Kaempferol exhibited anti-proliferative effects in endometrial carcinoma cells through apoptosis and cell cycle arrest, and was able to decrease migration and invasion trends in these cells [340]. In immortalized human retinal pigment epithelial (ARPE-19) cells, treatment with kaempferol was able to decrease cell migration through ERK1/2 signaling [346]. Kaempferol-conjugated gold nanoclusters (K-AuNCs) were developed by Govindaraju et al [424] as a potential anti-cancer drug delivery system, and they demonstrated that K-AuNCs targeted A549 lung cancer cells and exhibited toxicity via nucleus damage.…”
Section: Kaempferolmentioning
confidence: 99%
“…Moreover, kaempferol inhibited metastasis of 786-O cells into the lungs by 87.4% in the SCID mice model [ 81 ]. In addition, kaempferol suppressed migration and invasion of ARPE-19 human retinal pigment epithelial cells via the reduction of protein expression and activity of MMP-2 mediated by increased levels of phosphorylated extracellular signal-regulated kinases 1/2 ERK1/2 [ 82 ].…”
Section: Targeting Metastatic Cancermentioning
confidence: 99%
“…Kaempferol has been shown to suppress migration and invasion in many cancers [ 5 , 13 , 14 , 23 ]. For instance, kaempferol inhibits the migration and invasion of human retinal pigment epithelial cells [ 24 ]. Recent studies have shown that kaempferol represses migration and invasion via various signaling pathways.…”
Section: Discussionmentioning
confidence: 99%